Kampen om sandheden – Klimavidenskab som aktivisme - Glerup, Cecilie; Degnbol, Marie Chimwemwe (Politik, 2014)
This paper shows how political cultures in uence the use of scienti c data in the construction of critique among climate change activists. Based on an ethnographic study of the Danish NGO, „ e Climate Move- ment in Denmark’s“, steering committee, it is shown how the members carefully choose speci c scienti c references in their work. ey are chosen based on two criteria. First, the committee’s perceived ideas about the references’ ability to convince the Danish population about the severe consequences of climate change. And second, the references’ ability to unite all citizens across political and social barriers in the battle. In its way of using science, the committee assumes that the entire nation would be united in solidarity, if they were not blinded by what we (with thanks to Marx and Engels) have chosen to call ‘false con ictuality’; the idea that con icting scienti c statements divide and confuse ordinary people which prevent them from protesting. Following this, it becomes the NGO’s task to enlighten and thereby unite. e focus on creat- ing consensus among citizens with di erent backgrounds and con icting interest is interpreted as a typical instance of traditional Danish ‘Consensus Culture’ where agreement is seen as a precondition for change. But the paper nally argues that it might prove di cult to create solidarity solely based on carefully chosen scienti c statements without any reference to cultural visions for a better common future.